2007
DOI: 10.1210/me.2006-0345
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 Differentially Regulates the Transcriptional Activity of the Glucocorticoid Receptor through Phosphorylation: Clinical Implications for the Nervous System Response to Glucocorticoids and Stress

Abstract: Glucocorticoids, major end effectors of the stress response, play an essential role in the homeostasis of the central nervous system and influence diverse functions of neuronal cells. We found that cyclin-dependent kinase 5 (CDK5), which plays important roles in the morphogenesis and functions of the nervous system and whose aberrant activation is associated with development of neurodegenerative disorders, interacted with the ligand-binding domain of the glucocorticoid receptor (GR) through its activator p35 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
117
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 63 publications
7
117
1
Order By: Relevance
“…This suggests that GR phosphorylation at S203 serves as a negative regulator of GR transcriptional activity in ASM cells. A similar observation was reported by Kino and colleagues, who found that the GR-S203A mutant dramatically increased GC-induced, GRmediated transactivation activities in human colorectal carcinoma cell line (HCT116) (45). Other differences found in our study are the fact that GR phosphorylation at S203 was mostly located in the cytoplasm of ASM cells (data not shown) and that the transfection of the mutated form of GR at S203 residues was associated with increased GR nuclear translocation ( Figure 4B).…”
Section: Discussionsupporting
confidence: 85%
“…This suggests that GR phosphorylation at S203 serves as a negative regulator of GR transcriptional activity in ASM cells. A similar observation was reported by Kino and colleagues, who found that the GR-S203A mutant dramatically increased GC-induced, GRmediated transactivation activities in human colorectal carcinoma cell line (HCT116) (45). Other differences found in our study are the fact that GR phosphorylation at S203 was mostly located in the cytoplasm of ASM cells (data not shown) and that the transfection of the mutated form of GR at S203 residues was associated with increased GR nuclear translocation ( Figure 4B).…”
Section: Discussionsupporting
confidence: 85%
“…Mechanisms resulting in GC resistance are rarely attributed to mutation of the GR but often attributed to the convergence of additional activated cell signaling components with the GR pathway. Such pathways include mitogen-activated kinases, protein kinase A, CDKs, and receptor tyrosine kinase (2,26,32,39,44). We show here the convergence of another pathway, the GSK-3␤ signaling pathway, which also exerts a form of cellular resistance to GC administration.…”
Section: Discussionmentioning
confidence: 61%
“…However, in addition to ligand binding, several recent studies provide evidence that cross talk from other signaling pathways are able to directly modulate the GR transcriptional responses by phosphorylating the GR (17). In fact, human GR phosphorylation by kinases, such as mitogen-activated protein kinases and cyclin-dependent kinases (CDKs), act to modulate the receptor protein stability, subcellular localization, protein interactions, and translational response (12,26,28,32,39,44,48). Interestingly, Rogatsky et al have previously shown that GSK-3␤-mediated phosphorylation of rat GR on threonine 171 can inhibit transcriptional activation (40).…”
mentioning
confidence: 99%
“…Other kinases are also reported as candidates for phosphorylating AR Ser-81 site, such as Cdk1, Cdk5 (5,8), and Cdk9 (5). With regard to Cdk5, it has been reported to regulate the transcriptional activity of glucocorticoid receptor through phosphorylation (37). In addition, there is evidence indicating that the amino acid sequence of the N terminus of Cdk5 contains the LXXLL motif, which corresponds to the sequence that cofactors utilize for interaction with nuclear receptors (38).…”
Section: Discussionmentioning
confidence: 99%